RESPIRATORY PARAMETERS OF COVID-19 PATIENTS AFTER THE PRONE POSITION - V. E Salvera Arnoldy; Julianus Yudhistira Tan; H Haris Pastiyanto (Nursing Current: Jurnal Keperawatan, 2021)
Hypoxemia is a condition when there is a lack of oxygen levels in the blood, especially from the arteries. In the early stages of COVID-19, several mechanisms such as intrapulmonary shunting, loss of pulmonary perfusion regulation, intravascular micro thrombus, and impaired diffusion capacity can contribute to the development of arterial hypoxemia, although there is no increase in respiratory work. The prone position is one of the most widely used therapies for patients with hypoxemia because the dorsal area has a large number of alveolar units that are not compressed by the weight of the abdominal cavity and mediastinum, thus creating a more efficient area for gas exchange. This study aimed to determine the effect of the prone position on changes in respiratory parameters of COVID-19 patients. This study used the descriptive correlation method on 27 respondents with purposive sampling. Each respondent was given a prone position for three hours and being observed before, during the three-hour, and after one hour of the prone position administration”. The results of the descriptive analysis of this study showed that the majority of respondents were middle adulthood (63%) with 70% of the respondents being male, 59% having a history of hypertension, and 85% experiencing coagulation disorders. The change in the mean respiratory rate during one hour of supination after three hours of prone position in males was greater than that in females although the mean decrease in oxygen saturation was the same. This shows that the prone position for three hours accompanied by oxygen therapy made an improvement in respiratory status in COVID-19 patients, although it needs further investigation with more respondents and different research methods.